Citizenship Behavior in the Workplace: An Exploration of Employee Motives - Kartika Nuradina; Aldinel Fikri; Diana Harding (Greenation International Journal of Tourism and Management, 2024)
This research explores the role of motives in explaining individual involvement in organizational citizenship behavior (OCB). Three motives of citizen behavior were identified: prosocial values (PV), organizational concern (OC), and impression management (IM). Scales that measured these motives and other variables known to covary with OCB were correlated with 5 dimensions of OCB. Questionnaires were administered to 112 employees of Bandung City Municipal Office. Prosocial values exhibited the strongest association with individual-focused OCB, while organizational concern displayed the strongest link with organization-oriented OCB. Each motive independently contributed to explaining variance in OCB. The results emphasize the significance of motives in understanding OCB.